The study on the damage evolution and size characteristics of gangue cemented backfill - Bin Guo; Pengfei Wu; Bing Liang; Jiaxu Jin (Case Studies in Construction Materials)
Structural backfill mining involves placing columnar, strip, or box-shaped backfill bodies at key locations in the mined-out area to form a stable ''backfill body - immediate roof'' composite bearing structure. However, this structure requires high demands on the size and strength characteristics of the backfill material. In this context, this study investigates the influence of size on the mechanical properties and damage failure of gangue cemented backfill (GCB) by creating cube specimens of different sizes. It also establishes a damage model for GCB at various sizes. The results show that: The uniaxial compressive strength initially increases and then decreases with the change in the size of the GCB specimens, and the failure mode transitions from splitting failure to X-shaped conjugate shear failure as the size increases. Size primarily influences the formation and propagation of internal cracks within the backfill, resulting in differences in acoustic emission events among specimens of different sizes. By introducing a compaction coefficient α, a damage model is constructed to represent the damage during the compaction stage of uniaxial compression for different-sized GCB specimens.